Revision of the Anthidiellum Cockerell, 1904 of China (Hymenoptera, Apoidea, Megachilidae, Anthidiini) - Niu, Ze-Qing; Ascher, John S.; Luo, A-Rong; Griswold, Terry; Zhu, Chao-Dong (Zootaxa, 2016)
The resin bees of the genus Anthidiellum Cockerell, 1904 are revised for China. Seven species are confirmed to occur in China including five new combinations: A. (Pycnanthidium) carinatum (Wu, 1962) comb. nov., A. (P.) coronum (Wu, 2004a) comb. nov., A. (P.) latipes (Bingham, 1897) comb. nov., A. (Clypanthidium) popovii (Wu, 1962) comb. nov., and A. (Anthidiellum) yunnanensis (Wu, 1962) comb. nov.. These five species had previously been classified as Trachusa (Paraanthidium), which is characterized by much larger-bodied bees (only four species of Trachusa (Paraanthidium) are confirmed to occur in China after this study; others reported in the literature were misplaced to genus). Additionally, Anthidiellum ludingensis Wu, 1993, and Anthidiellum (Anthidiellum) xinjiangensis Wu, 2004b, are removed from Anthidiellum forming the new combinations Pseudoanthidium (Pseudoanthidium) ludingense (Wu, 1993) and P. (P.) xinjiangense (Wu, 2004b), thus extending the range of the genus in China to include Sichuan. Illustrations and a key to known Chinese Anthidiellum species are provided.